POLIMORFISME GEN ANGIOTENSIN I CONVERTING ENZYME (ACE) INSERSI/DELESI (I/D) DAN HEIPERTENSI PADA PENDUDUK MLATI SLEMAN (Tinjauan Pustaka dan Laporan Penelitian) - , SUTARSO KAMAJAYA; , Prof. Dr. dr. Moch. Sja'bani, M.Med.Sc., SpPD-KGH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Hypertension is considered as a multifactorial trait resulting from a combination of environmental and genetic factors. Genetic mutation is rare, when genetic mutation more than 1% population called as polymorphism. There are many genes polymorphism associated with hypertension. Polymorphism of the genes coded in the component of Renin-angiotensinaldosteron system (RAAS) are potential influence essential hypertension. The popular polymorphism was a insertion/deletion (I/D) in ACE gene. Recent studies showed that DD genotype and D allele have been associated with higher prevalence of hypertension. There is no data reported so far about the possible effect of I/D polymorphism of the ACE gene and hypertension in Javanese population based on community. There is a wide variation in ACE gene polymorphism among the ethnics. Objective: To investigate ACE gene polymorphism in hypertensive subjects in Javanese population. Methode: A case control study by matching of sex and age, was conducted in August 2008-July 2009, based on community at district of Sleman-Yogyakarta. The covered subjects were 12073 over 17 years, after selected by aged of 30-59 years old, we get 7695 people and grouped in normotension, pre-hypertension and hypertension. Stratified randomize was done to select 51 for hypertension and 51 normotension involving this study. Genotypes based on the polymorphisms (II/ID/DD) using a polymerase chain reaction (PCR) methode, at Biochemistry Laboratory Faculty of Medicine Gadjah Mada University Yogyakarta. Results: The genotype frequencies in hypertensive group versus normal were II 23(45.0%) vs 37(72.5%), ID 25(49.0%) vs 13(25.5%) and DD 3(6.0%) vs 1(2.0%) p=0.043. The allele frequencies were I allele 35(68.5%) vs 43(84.5%), D allele 16(31.5%) vs 8(15.5%), p=0.038. Logistic regression analysis showed that D allele as a risk factor for hypertension. Conclusion: Frequencies of ID and DD genotypes and D allele ACE gene in hypertensive subject were higher than normotensive subjects. The D allele of the ACE gene was a predisposing factor in hypertension.